Role of the exposome in mental disorders: a scoping review protocol - Maria Ruiz-Castell; Coralie Dessenne; Gloria A Aguayo; Claudia Gutierrez-Ortiz; Babul Hossain (BMJ Open)
Introduction The development of mental disorders is multifactorial across the lifespan. The introduction of the exposome concept has enhanced the understanding of life-course environmental factors by encompassing the totality of environmental exposures. While most studies on chronic diseases have applied a single-exposure approach, the exposome approach remains underutilised in mental disorder research. There is a need to better recognise the environmental factors considered in exposome analysis of mental disorders, the methodologies used and the gaps reported. This scoping review aims to map the evidence on the relationship between the exposome and mental disorders across the lifespan, identifying and describing the methodologies used and highlighting the gaps reported.Methods and analysis This scoping review will follow PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and the Population-Concept-Context approach. It will include observational and interventional studies involving populations of all ages in the community or healthcare settings. The search strategy will contain indexed terms in MEDLINE and will be adapted for CINAHL (EBSCO), Scopus, Embase and PsycINFO without restrictions on language or date of publication. For the selection of articles, two independent researchers will screen articles by title and abstract, followed by a full-text assessment. Afterwards, the extracted data will be summarised using a narrative and descriptive analysis.Ethics and dissemination Ethics approval is not required for this scoping review. Dissemination activities will include peer-reviewed publications and academic presentations.